2009
DOI: 10.1182/blood-2009-04-219253
|View full text |Cite
|
Sign up to set email alerts
|

Human Siglec-10 can bind to vascular adhesion protein-1 and serves as its substrate

Abstract: Leukocytes migrate from the blood into areas of inflammation by interacting with various adhesion molecules on endothelial cells. Vascular adhesion protein-1 (VAP-1) is a glycoprotein expressed on inflamed endothelium where it plays a dual role: it is both an enzyme that oxidizes primary amines and an adhesin that is involved in leukocyte trafficking to sites of inflammation. Although VAP-1 was identified more than 15 years ago, the counterreceptor(s) for VAP-1 on leukocytes has remained unknown. Here we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 33 publications
2
73
0
Order By: Relevance
“…16 Recombinant VAP-1 was purified from stable CHO-VAP-1 transfectants using immunoaffinity purification as described. 26 We found that the optimal final serum dilutions are 1:100 and 1:34 for the 96-and 384-well formats, respectively, and the linear range of the assay is from 2.0 to 86.0 nmol/mL/h. The intraassay and interassay variations were 4% and 10%, respectively, for the 96-well format (tested by measuring triplicates of 9 serum samples in 2 to 4 independent experiments), and 8% and 15%, respectively, for the 384-well format (tested by measuring duplicates of 32 serum samples in 7 independent experiments).…”
Section: Measurement Of Svap-1 Activitymentioning
confidence: 96%
“…16 Recombinant VAP-1 was purified from stable CHO-VAP-1 transfectants using immunoaffinity purification as described. 26 We found that the optimal final serum dilutions are 1:100 and 1:34 for the 96-and 384-well formats, respectively, and the linear range of the assay is from 2.0 to 86.0 nmol/mL/h. The intraassay and interassay variations were 4% and 10%, respectively, for the 96-well format (tested by measuring triplicates of 9 serum samples in 2 to 4 independent experiments), and 8% and 15%, respectively, for the 384-well format (tested by measuring duplicates of 32 serum samples in 7 independent experiments).…”
Section: Measurement Of Svap-1 Activitymentioning
confidence: 96%
“…Bovine VAP has been shown to bind, but not oxidize, lysine and soluble elastin in vitro in the presence of H 2 O 2 and thereby inhibit the catalytic turnover of benzylamine (13). Recently, a binding partner for VAP-1 on the surface of lymphocytes has been identified from phage libraries displaying decapeptides (14). Siglec-10 (sialic acid-binding Ig-like lectin-10), shown to bind specifically to recombinant VAP-1, is the first leukocyte ligand identified for the enzyme (14).…”
mentioning
confidence: 99%
“…Recently, a binding partner for VAP-1 on the surface of lymphocytes has been identified from phage libraries displaying decapeptides (14). Siglec-10 (sialic acid-binding Ig-like lectin-10), shown to bind specifically to recombinant VAP-1, is the first leukocyte ligand identified for the enzyme (14). Binding results in H 2 O 2 production, suggesting that Siglec-10 acts as a substrate.…”
mentioning
confidence: 99%
“…Given its broad immune distribution, suppression by CD52 released from CD52-expressing regulatory CD4 T cells may not be restricted to T cells only, but may also extend to a broader population of peripheral blood mononuclear cells that include dendritic cells, monocytes and B lymphocytes. As human Siglec-10 also binds to vascular adhesion protein-1 to act as its substrate and to mediate lymphocyte binding to the endothelium, 9 binding of CD52 to siglec-10 could also potentially modify the inflammatory microenvironment.…”
mentioning
confidence: 99%